Structural changes in the Philippine pig industry and their environmental implications - Catelo, Maria Angeles O.; Narrod, Clare; Tiongco, Marites (International Food Policy Research Institute, 2008)
Pig production in the Philippines has intensified in the urban and peri-urban areas in response to a radical structural change in the pig industry and a growing demand for pork products. Alongside this rapid growth is the emergence of societal concern about the increasing negative environmental externalities that the industry produces, particularly those related to the disposal of waste and dead animals. Pig producers are said to benefit from negative externalities when they do not bear the full social costs of their business enterprise. Non-internalization of such externalities occurs when pig producers receive payment for their output while not investing in pollution abatement or not making compensatory payments to surrounding communities affected by their production processes. In some cases, producers are able to recycle all nutrients from swine production on-farm through various cropping mechanisms. In other cases, pig production is so large that there is no land to properly dispose of such by-products without some environmental mitigation effort. Failure to implement any sort of measure will most likely lead to an environmental externality. To determine whether a farmer has the ability to utilize all manure produced on-farm, we use a mass balance calculation approach in this paper. Results for the mass balance calculations suggest that, in general, smaller farms generate less excess nutrients per hectare than larger farms. This is because most small-scale pig farms are mixed systems where some croplands are available for nutrient assimilation. Large commercial farms tend to be ?pure land-intensive? systems. We used a Tobit regression analysis to determine the factors affecting environmental mitigation expenditures of pig farms. Results of the regression showed that smaller farms tend to respond to opportunities to make use of manure as fertilizer on their own farms and crops. For large farms, no single factor significantly influenced mitigation costs. An interpretation of why this is so or what this result implies apparently cannot be achieved without ambiguity. Thus, we do not attempt to do so and we leave the matter for further investigation. With respect to the effects of production arrangement on environmental capture, the factors that significantly influenced mitigation costs varied between independent and contract farms. Only the operation of croplands mattered for independent producers. For contract farms, lands that are classified as agricultural carried the expected positive coefficient sign. Further, farmers in the industrial pig sector, which is concentrated in peri-urban areas favored by market access or feed availability, may consider being located as close as possible to cropland that they can use to dispose of the wastes in pig production. Policy options include zoning, mandatory nutrient management plans, licensing or limiting the number of animals raised per production unit, and contractual agreements between livestock producers and crop farmers. The effectiveness of such regulations will depend largely on the degree to which they are enforced and whether they are accompanied by a well-developed system of education and extension with focus on proper manure management systems and dead animal disposal.